I-APPROXIMATION PROPERTIES OF CERTAIN CLASS OF LINEAR POSITIVE OPERATORS - Mahmudov, Nazim Idrisoglu; Ozarslan, Mehmet Ali; Sabancigil, Pembe (Akademiai Kiado Zrt, 2011)
In this paper we study I-approximation properties of certain class of linear positive operators. The two main tools used in this paper are I-convergence and Ditzian-Totik modulus of smoothness. Furthermore, we define q-Lupas-Durrmeyer operators and give local and global approximation results for such operators.
Keywords: I-convergence; Ditzian-Totik modulus of smoothness; positive operator; q-Lupas-Bernstein operator; q-Lupas-Durrmeyer operator